CXCR4 and MMP-9 Immunoexpression are Associated with Metastasis in Infiltrating Urothelial Carcinoma of The Bladder - Siska Dwiyantie Wahyuni; Sri Suryanti; Hasrayati Agustina; Bethy Suryawathy Hernowo (National Cancer Center - Dharmais Cancer Hospital, 2022)
Background: Infiltrating urothelial carcinoma of the bladder (IUCB) is an aggressive urinary tract cancer. Most of the patients were diagnosed with advanced stages, and many have metastasized. Metastasis is responsible for 90% of cancer deaths compared to the primary tumor itself. In previous research, the expression of CXCR4 and MMP-9 has been suggested to correlate with metastasis and prognosis in several cancers. This study aimed to analyze the association of CXCR4 and MMP-9 expression with metastasis in infiltrating urothelial carcinoma of the bladder. Methods: This cross-sectional study included 40 selected paraffin-embedded tissue blocks from histopathologically diagnosed IUCB patients, consisting of 20 cases of non-metastasizing and 20 cases of metastasizing IUCB. Immunohistochemical staining for CXCR4 and MMP-9 was performed in all cases. All data were analyzed using the Chi-Square test with p < 0.05 of a significant level and then processed using SPSS 24.0 for Windows.Results: High CXCR4 immunoexpression was found in 18 (45%) of all cases, and high MMP-9 immunoexpression was found in 19 (47.5%) cases. High immunoexpression of CXCR4 and MMP9 in infiltrating urothelial carcinoma of the bladder showed significant association with metastasis (p < 0.05). The stepwise logistic regression analysis revealed that both CXCR-4 and MMP-9 immunoexpressions were independent prognostic factors for metastasis.Conclusions: CXCR4 and MMP-9 play a role in the metastatic process in infiltrating urothelial carcinoma of the bladder.